Welcome, Video Dance, 2016, - Antoniou, Klitsa (My University, 2026)
Duration: 1:00, Open Borders Project Video Dance Festival of Burgundy Art Installation and Sculptures: Klitsa Antoniou Choreography and performance: Elena Christodoulidou https://www.facebook.com/videodanceburgundy/videos/10153702289844532/